Simultaneous Multi-channel Data Acquisition and Storing System - Abdallah, M.; Elkeelany, O. (International Conference of Computing in Engineering, Science and Information, 2009)
In this paper, a novel simultaneous multichannel data acquisition system is proposed. Analog signals are applied to an analog multiplexer with a single analog to digital converter. The target technology of implementing the proposed design is the field programmable gate array (FPGA). The analog-to-digital converter interface and the flash memory driver are implemented in the FPGA using hardware description language. The synthesized prototype used only 11% of the total logic elements (of Altera CycloneII, EP2C35F672C-6N FPGA) and 15% of its total memory bits. The worst-case prorogation delay observed for the system is 12.04 ns, which is less than the 50 MHz clock period of 20 ns. The Cyclone-II FPGA consumes power as low as 12 mW. The SNR of the recorded signal is 70 dB. The proposed system can be used in various applications that require simultaneous multi-channel data acquisition system such as biomedical engineering.